PENGEMBANGAN KOMIK DIGITAL CERITA DONGENG PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SEKOLAH DASAR - Novfan Rahmat Ramadhan; Wawan Priyanto; Mei Fita Asri Untari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a valid and practical digital comic medium of fairy tales for the Indonesian Language subject in third-grade elementary school. The type of research used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted at two elementary schools: SDN Gayamsari 01 and SDN Karangtempel. The results of the validation tests by media experts and material experts obtained a percentage of 95.3%, which falls within the interval of 81%–100% and is categorized as "highly feasible." Meanwhile, the practicality test results by teachers obtained a percentage of 93.3%, and the practicality test results by students reached 98.6%, both of which fall within the interval of 81%–100% with the category of "highly feasible." Therefore, the developed digital comic of fairy tales is declared highly feasible for use as a learning medium in the Indonesian Language subject for third-grade elementary school.